(untitled) (Ocean and Coastal Research, 2020)
Bacteria with lipolytic activity are widespread in the marine environment. These organisms can be usedas a source of lipases with activity in unusual conditions such as low temperatures and high salinities.These characteristics allow them to be applied to several industrial processes and products includingwastewater treatment and detergent production. In this context the lipolytic activity of bacteria isolatedfrom deep-sea sediments of the South Atlantic was evaluated. Among the collection studied, two strains,Halomonas sulfidaeris LAMA 838 and Marinobacter excellens LAMA 842, were selected for further analysisconcerning their growth and lipolytic activity in different temperatures and culture media. Both strainswere characterized as mesophiles: H. sulfidaeris LAMA 838 grew best at 30ºC, while M. excellens LAMA 842showed a maximum growth rate between 20 and 25ºC. Maximum lipolytic activity for both microorganismswas observed above 45ºC, but only M. excellens LAMA 842 had lipolytic activity at low temperatures (5ºC) aswell. Considering the culture media employed, H. sulfidaeris LAMA 838 grew better in marine broth withoutTween 40, while M. excellens LAMA 842 grew best in marine broth supplemented with Tween 40. Bothorganisms had maximum lipolytic activity in rich or minimal media supplemented with Tween 40. Theseresults demonstrate the potential of deep-sea bacteria as sources of lipases and indicate conditions thatmay be used in their cultivation and for the production of industrially relevant enzymes.